Implementasi Teori Wihda dan Furu’iyah dalam Pengajaran Bahasa Arab di Pesantren Modern dan Shalaf Sulawesi Selatan - Kasim, Amrah; Sakka, Abdul Rahman; Pallawagau, Baso; Rahim, Abdul (Shaut al Arabiyyah, 2023)
This research discusses the application of wihdah and furu‟iyah theory in teaching Arabic in modern pesantren and salaf in South Sulawesi. The purpose of this study is to determine the efficiency of the use of wihdah and furu‟iyah theory in teaching Arabic in modern pesantren and salaf in South Sulawesi. This research is a library research study that is qualitative and rationalistic in style. This type of research uses qualitative analysis with the ability to build arguments. The data are not sensory empirics but rather thoughts, opinions, theories constructed with a certain system of logic, ordinary in historical, textual, contextual, intextual genetic form. The results showed that the application of nazariyah al-Wihdah is very important in learning Arabic at the pesantren Ummul Mukminin in Makassar, even though there are obstacles in it. This is in accordance with the achievement of the expected Arabic learning objectives. Meanwhile, the application of nazariyah al-Furu‟ in the mastery of maharat al-lugah at the pesantren DDI Abdurrahman Ambo Dalle Mangkoso in mastering maharat al-Lugah is a guide in achieving learning goals so that students can read Arabic textbooks, in addition to the implementation of nazariyah al-Furu‟ enacted because it was considered a mandate of the founder of the institution.